2012
DOI: 10.1159/000337743
|View full text |Cite
|
Sign up to set email alerts
|

Murine T Cell-Derived Contractile Activity for Bronchial Smooth Muscle Cells

Abstract: Background: Adoptive transfer of helper T (Th) cells conferred a late asthmatic response upon antigen challenge. A possible production of a contractile activity for bronchial smooth muscle (BSM) by activated Th cells was examined. Method: Murine Th clones were stimulated with immobilized anti-CD3 antibody in the presence or absence of anti-CD28 antibody. Culture supernatants were dialyzed and then applied to the collagen gels containing cultured human BSM cells. Results: Culture supernatants of activated but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…It was shown that IL-2 activated T lymphocytes induced proliferation and migration of muscle precursor cells. An additional recent study reported that supernatants of cultured anti-CD3 activated murine TH (T helper) lymphocytes induced the contraction of human bronchial smooth muscle cells [16]. …”
Section: Introductionmentioning
confidence: 99%
“…It was shown that IL-2 activated T lymphocytes induced proliferation and migration of muscle precursor cells. An additional recent study reported that supernatants of cultured anti-CD3 activated murine TH (T helper) lymphocytes induced the contraction of human bronchial smooth muscle cells [16]. …”
Section: Introductionmentioning
confidence: 99%
“…T cells are capable of producing bronchoactive mediators, including acetylcholine [135]. Moreover, we identified a higher-molecular-weight substance produced by murine T cells that induces the contraction of bronchial smooth muscle cells [136]. Allergen-induced late-phase airway obstruction was observed in mice transferred with OVA-reactive T cell clones [137].…”
Section: Th9 Cells Induce Bhr Accompanied By But Not Dependent On mentioning
confidence: 99%